2013
DOI: 10.1186/bcr3458
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α/GPER signaling mediates the expression of VEGF induced by hypoxia in breast cancer associated fibroblasts (CAFs)

Abstract: IntroductionCarcinoma-associated fibroblasts (CAFs) play a pivotal role in cancer progression by contributing to invasion, metastasis and angiogenesis. Solid tumors possess a unique microenvironment characterized by local hypoxia, which induces gene expression changes and biological features leading to poor outcomes. Hypoxia Inducible Factor 1 (HIF-1) is the main transcription factor that mediates the cell response to hypoxia through different mechanisms that include the regulation of genes strongly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
173
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(184 citation statements)
references
References 63 publications
(69 reference statements)
5
173
1
Order By: Relevance
“…However, studies have also reported that THD has anti-inflammatory, immunomodulatory, and anti angiogenic effects (16). The effects of THD on proliferation of colon cancer cells are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have also reported that THD has anti-inflammatory, immunomodulatory, and anti angiogenic effects (16). The effects of THD on proliferation of colon cancer cells are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is one of the target genes of HIF-1α. HIF-1α promotes the transcription of target gene VEGF, and regulates angiogenesis in tumors under hypoxic conditions (15,16). Therefore, HIF-1α may reduce the possibility of recurrence and metastasis of tumor cells if the formation of new blood vessels in tumor tissue can be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased expression of HIF-1α is associated with slower cell growth and tumor angiogenesis (12,31). HIF-1α and VEGF-A expression are strongly associated with cancer progression and angiogenesis (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of HIF-1α is associated with slower cell growth and tumor angiogenesis (12,31). HIF-1α and VEGF-A expression are strongly associated with cancer progression and angiogenesis (12)(13)(14). In our study, the control group demonstrated marked expression of p-mTOR, which is the activated form of mTOR and its downstream protein, HIF-1α and VEGF-A, while the high and low-dose aspirin and everolimus groups effectively inhibited the expression of p-mTOR, HIF-1α and VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation